Synthesis, characterisation and stability of superparamagnetic maghemite nanoparticle suspension - Nurdin, Irwan; Johan, Mohd Rafie; Yaacob, Iskandar Idris; Ang, Beechin; Andriyana, Andri (Maney Publishing, 2014)
Maghemite nanoparticles were synthesised using the co-precipitation method and characterised by various techniques, including X-ray diffraction, transmission electron microscopy, alternating gradient magnetometry, dynamic light scattering and zeta potential. The stability of the suspension was monitored by measuring the particle size distribution and zeta potential using dynamic light scattering over a period of few months. The pattern obtained from X-ray diffraction confirmed that the particles were maghemite with crystallite size of 94 nm. Transmission electron microscopy observations and analyses showed that the mean physical size of the nanoparticles was 95 nm. The nanoparticles show superparamagnetic behaviour with magnetisation value at ±10 kOe of 3218 emu g-1. The intensity averaged particle size of as-synthesised maghemite nanoparticles was 453 nm. The suspension was stored for periods of 2, 4 and 8 months. The intensity averaged sizes were 471, 505 and 521 nm respectively. No sedimentation was observed. The suspension's zeta potential value was 446 mV for as-synthesised sample and 433, 427 and 418 mV for sample after storage period of 2, 4 and 8 months, respectively. This indicated that the suspension was very stable.